Perbandingan Sistem Penilaian Pediatric Appendicitis Score dan Alvarado Score dalam Memrediksi Kasus Apendisitis pada Anak - Sela, Gabriel M.; Lampus, Harsali F. Lampus; Rawung, Rangga B. V. (Medical Scope Journal, 2025)
Abstract: Appendicitis is the most common reason for emergency abdominal surgery. The biggest challenge lies in making a prompt and accurate diagnosis to prevent life-threatening complications, especially in children who often find it difficult to express their pain. In this context, clinical scoring systems such as the Pediatric Appendicitis Score (PAS) and Alvarado Score (AS) serve as important tools for clinicians in aiding the diagnosis of appendicitis in children. This study aimd to compare PAS and AS systems in predicting appendicitis cases in children. This was a literature review study searching articles from Google Scholar and PubMed databases. The search resulted in 10 articles that met the inclusion and exclusion criteria. The average accuracy of PAS was found to have a sensitivity of 82.16%, specificity of 55.26%, PPV of 82.95%, NPV of 53.41%, and DA of 86.17%. Meanwhile, the AS had a sensitivity of 78.52%, specificity of 64.75%, PPV of 84.15%, NPV of 53.21%, and DA of 81.58%. In conclusion, Pediatric Appendicitis Score has a higher sensitivity compared to the Alvarado Score. With its higher sensitivity, PAS is more effective in identifying cases of appendicitis, making it a better tool for early detection in children. Keywords: Pediatric Appendicitis Score; Alvarado Score; appendicitis Abstrak: Apendisitis merupakan penyebab paling umum dari pembedahan darurat pada perut. Tantangan terbesar ialah membuat diagnosis yang cepat dan akurat untuk mencegah komplikasi yang mengancam jiwa, terutama pada anak yang sering kali sulit mengungkapkan rasa sakit. Dalam konteks ini, sistem skoring klinis seperti Pediatric Appendicitis Score (PAS) dan Alvarado Score (AS) menjadi alat penting bagi klinisi untuk membantu diagnosis apendisitis pada anak. Penelitian ini bertujuan untuk membandingkan sistem PAS dan AS dalam memrediksi kasus apendisitis pada anak. Jenis penelitian ialah suatu tinjauan pustaka dengan artikel yang dicari melalui database Google Scholar dan PubMed. Hasil pencarian mendapatkan 10 artikel yang memenuhi kriteria inklusi dan eksklusi. Rerata akurasi PAS ditemukan memiliki sensitivitas sebesar 82,16%, spesifisitas 55,26%, PPV 82,95%, NPV 53,41%, dan DA 86,17%. Sementara itu, AS memiliki sensitivitas sebesar 78,52%, spesifisitas 64,75%, PPV 84,15%, NPV 53,21%, dan DA 81,58%. Simpulan penelitian ini ialah Pediatric Appendicitis Score memiliki sensitivitas yang lebih tinggi dibandingkan Alvarado Score. Dengan sensitivitas yang lebih tinggi, PAS lebih efektif dalam mengidentifikasi kasus apendisitis, yang menjadikannya alat yang lebih baik untuk deteksi dini pada anak. Kata kunci: Pediatric Appendicitis Score; Alvarado Score; apendisitis